PREDICTIVE ACCURACY OF POSSUM IN ASSESSING MORBIDITY AND MORTALITY AFTER EMERGENCY LAPAROTOMY (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To assess the predictive accuracy of the Physiological and Operative Severity Score for the Enumeration of Mortality and Morbidity (POSSUM) for the prediction of 30-day morbidity and mortality in patients undergoing emergency laparotomy. Study Design: Prospective cross-sectional study. Place and Duration: This study was carried out at Indus Medical College Tando Muhammad khan Pakistan, from April 2025 to April 2026 Methods: The study included patients aged 15–75 years who underwent emergency laparotomy, excluding polytrauma and immunocompromising disease, including chronic liver disease, chronic renal failure, COPD, asthma, HIV, malignancy, and genetic diseases. A total of 146 consecutive patients were entered. Demographic and clinical data were obtained, POSS physiological and operative scores were computed, and a 30-day follow-up was conducted to assess morbidity and mortality. Data were summarized by mean ± SD or median and IQR, frequencies were used for qualitative data, and discrimination was assessed using ROC curves. Results: The cohort included 88 males (60.3%), with a mean age of 46.8 ± 14.5 years. The most common indications were perforation peritonitis (42.5%) and intestinal obstruction (31.5%). Thirty-day mortality was 18 patients (12.3%), and morbidity was 72 patients (49.3%). The ROC curve demonstrated satisfactory discrimination for mortality (AUC 0.782, p < 0.001) and moderate prediction for morbidity (AUC 0.618, p = 0.092). Conclusion: POSSUM is a useful predictor of 30-day mortality but not morbidity in the emergency laparotomy population. Although useful for mortality risk stratification, greater sophistication or localization of models is necessary to predict morbidity.